Health and subjective views on aging: longitudinal findings from the ActiFE Ulm study - Schönstein, Anton; Dallmeier Rojas, Dhayana Elizabeth; Denkinger, Michael D.; Rothenbacher, Dietrich; Klenk, Jochen; Bahrmann, Anke; Wahl, Hans-Werner (The journals of gerontology. Series B, Psychological sciences, social sciences, 2021)
AbstractObjectives. Previous research supports that subjective views on aging (VoA), such as older subjective age (SA) and negative attitudes toward own aging (